2021
DOI: 10.3390/biomedicines9081037
|View full text |Cite
|
Sign up to set email alerts
|

Variable Changes of Circulating ANGPTL3 and ANGPTL4 in Different Obese Phenotypes: Relationship with Vasodilator Dysfunction

Abstract: Obesity associates with premature atherosclerosis and an increased burden of cardiovascular disease, especially when accompanied by abnormalities of lipid and glucose metabolism. Angiopoietin-like (ANGPTL)3 and ANGPTL4 are metabolic regulators, whose upregulation is associated with dyslipidemia, insulin resistance and atherosclerosis. We analyzed, therefore, changes in circulating ANGPTL3 and ANGPTL4 in obese patients with different metabolic phenotypes and their relation with impaired vasodilator reactivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…However, contrary to our results, this was not the case for MHO. ANGPTL4 was significantly elevated in all obese subgroups in their work in contrast to our results [60]. In line with the findings of Schinzari et al, our results suggest a different mechanism related to the dysregulation of ANGPTL3 and ANGPTL4 in patients with excessive fat mass.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, contrary to our results, this was not the case for MHO. ANGPTL4 was significantly elevated in all obese subgroups in their work in contrast to our results [60]. In line with the findings of Schinzari et al, our results suggest a different mechanism related to the dysregulation of ANGPTL3 and ANGPTL4 in patients with excessive fat mass.…”
Section: Discussionsupporting
confidence: 85%
“…It is worth mentioning here that previous works measuring ANGPTL3 levels in insulin resistance states such as obesity and T2D have produced conflicting results. Most studies report increased circulation of ANGPTL3 in obese or T2D patients [60,61], while other studies have found that ANGPTL3 levels are not higher in obese subjects than in controls [62].…”
Section: Discussionmentioning
confidence: 96%
“…Based on our data, it is probable that the effects of these hepatokines on adipocytes synergize, together with other pathological mechanisms, to promote fat mass expansion and obesity. Circulating levels of AHSG [ 68 , 69 ], ANGPTL4 [ 70 , 71 ] and LECT2 [ 14 , 72 , 73 ] were previously demonstrated to correlate with obesity, BMI or waist circumference in humans. Although these hepatokines are predominantly expressed by the liver, mouse and human adipocytes were also reported to produce them [ 74 , 75 , 76 , 77 ], therefore suggesting both endocrine and paracrine action of these factors on AT homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action involves a complex of Angptl3 with the related protein Angptl8, that promotes Angptl3 effects [ 120 , 122 , 123 ]. Beyond lipid-lowering, inhibition of Angptl3 was shown to improve endothelial function [ 124 ]. This effect may be mediated indirectly through improved lipid levels, but also directly by binding endothelial integrin v3, and by stimulating Wnt/-catenin signaling [ 12 ].…”
Section: Novel Treatments For Lipid Disorders: Proprotein Convertase ...mentioning
confidence: 99%